Difficulties in translating business news at business column of dantri international news (dtinews.com.vn) = Những khó khăn trong việc dịch các bài báo kinh tế trong mục business của trang báo điện tử dân trí quốc tế (dtinews.com.vn) - Trần, Thị Phương (2021)
Along with the rapid development of information technology, the newspaper has also begun a period of development to meet people‟s information demands about every factor of life, both domestically and internationally. Therefore, to provide interesting and helpful international articles, a question for news agencies to consider is how to produce successful translation from Vietnamese to English and vice versa. This has led to the problems in translating news articles, and specifically, the difficulties that translators face in dealing with translation of news. As a way to help the translators out, this research aims at finding out the most prominant difficulties that translators have to overcome in translating news articles. However, newspapers in general cover almost every field of life; therefore it would be very difficult and complicated for the researcher to gain insights into every field. After thinking carefully to find out the most relevant factor in daily life, the researcher decided to focus on economic news articles only, and carry out the research at Dantri--one of the most popular and reliable news agencies in Vietnam. This research report consists of three main parts. It begins with the introduction, which states the rationale, aims, scope, and methods of the study. Part two includes three chapters, the first of which reviews the related literature, the second presents the study in details and the third deals with major findings from the data analysis. Part 4 three is the conclusion, which summarizes the whole study and gives suggestions for further research.